2014
DOI: 10.1002/hipo.22359
|View full text |Cite
|
Sign up to set email alerts
|

The metabotropic glutamate receptor, mGlu5, is required for extinction learning that occurs in the absence of a context change

Abstract: The metabotropic glutamate (mGlu) receptors and, in particular, mGlu5 are crucially involved in multiple forms of synaptic plasticity that are believed to underlie explicit memory. MGlu5 is also required for information transfer through neuronal oscillations and for spatial memory. Furthermore, mGlu5 is involved in extinction of implicit forms of learning. This places this receptor in a unique position with regard to information encoding. Here, we explored the role of this receptor in context-dependent extinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 71 publications
(88 reference statements)
2
39
0
Order By: Relevance
“…The floor and odor context were also kept constant during this time. On days 1 through 3, the reward probability was reduced in a stepwise manner from 100% to 25% to augment extinction resistance, as described previously (André et al, 2015 ). In conjunction with the reward probability reduction, the time limit for reaching the arm was also reduced from 2 min to 30 s Learning criterion was deemed to be acheived when the animal had successfully entered the correct arm on 8 of the final 10 trials of a given experiment day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The floor and odor context were also kept constant during this time. On days 1 through 3, the reward probability was reduced in a stepwise manner from 100% to 25% to augment extinction resistance, as described previously (André et al, 2015 ). In conjunction with the reward probability reduction, the time limit for reaching the arm was also reduced from 2 min to 30 s Learning criterion was deemed to be acheived when the animal had successfully entered the correct arm on 8 of the final 10 trials of a given experiment day.…”
Section: Methodsmentioning
confidence: 99%
“…Current reports suggest that is that the hippocampus is particularly important for context-dependent extinction (Kalisch et al, 2006 ). Most studies have examined this with regard to fear-extinction (Alvarez et al, 2008 ; Lang et al, 2009 ; Maren et al, 2013 ), but recently, it was demonstrated that extinction learning in an appetitive context is also likely to involve the hippocampus (André et al, 2015 ). In rodents, context-dependent spatial learning, as well as hippocampal synaptic plasticity that is triggered by spatial learning, is supported by β-adrenergic receptors (Kemp and Manahan-Vaughan, 2008 ; Hagena and Manahan-Vaughan, 2012 ; Goh and Manahan-Vaughan, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…At a certain point, the original memory and associated behavior must be suppressed, a process known as extinction learning [1]. According to several authors, the extinction process in the water maze would follow the same laws that govern instrumental learning [2], and even those which determine conventional classical and operant conditioning, so we might think that similar processes would underlie spatial and nonspatial associative learning [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…During a subsequent extinction phase, this rat can choose between at least four equally non-reinforced behaviors: turn left, turn right, return to the starting point before reaching the decision point, and refuse to leave the starting point altogether. Nevertheless, a typical analysis focuses only on the cessation of the previously conditioned response, in this case, turning right (28,29) . In this way, the effect of extinction learning on choice behavior remains undisclosed.…”
Section: Introductionmentioning
confidence: 99%
“…A further major problem for understanding the cognitive processes and neural mechanisms underlying operant extinction is the tradition of pooling and averaging across subjects and sessions. Such analyses not only conceal the complexity of behavior during a learning task (28,(31)(32)(33)(34), but also obscure the dynamics of learning within and across sessions (18,19) . Considering this variability is of particular importance for three main reasons.…”
Section: Introductionmentioning
confidence: 99%